Metal pollution status and health risk assessment of beach sediments along the Mersin coast, Turkey - Özbay Özgür; Akçay İsmail (Oceanological and Hydrobiological Studies)
In the present study, the ecological risk assessment of metal contamination in beach sediments along the Mersin coast was determined using the metal contents of beach sediments in Mersin, Kızkalesi, Susanoğlu and Taşucu region obtained between 2006 and 2009. Furthermore, the potential health risk assessment for ingestion and dermal contact pathways of adults and children was determined. Ecological risk assessment of heavy metals showed that there is no pollution in the beach sediments for the metals Cu, Pb and Zn for the all studied coasts. However, the high ecological risk indices calculated in this study strongly suggested an apparent Cd, Cr and Ni pollution in the studied beach sediments due to natural and anthropogenic contamination. Study findings indicated the HI values were greater than 1 for the metal Cr. The TCR values were higher than 1.00E-04 for the metals Cr and Ni calculated for adults, and for the metal Cu, Cr and Ni calculated for children, respectively. All these findings showed that there is a high carcinogenic risk for adults and children resident in the Mersin province from carcinogenic Cr and Ni whilst the studied coasts have additional health risks to children from carcinogenic Cu.